The Impact of Foot Arch Morphology on Risk of Overuse Injuries in Amateur Runners: A Prospective Biomechanical Study - Alshwekany, Saeed; Alarfaj, Yosuf Yaqub; Musaed, Sultan; Faraj, Fatma; Mahzari, Qasem Abdulrahman; Alhablani, Manea; Alamri, Dakheal Allah Fardan; Almutairi, Sarah; Khalil, Tahani; Albalawi, Amal (Journal of Posthumanism, 2025)
The log arch structure significantly influences lower limb movement and response to repetitive stress, particularly among non-elite runners and physical activity practitioners. Current research has inadequately explored the relationship between foot structure and injury risk, as blood DNA sequencing has not definitively linked pes planus (flat foot) and pes cavus (high arch) to injury potential. This research investigates the connections between foot structure morphology, intrinsic foot muscle power, and genetic elements (SNPs) concerning repeated strain injuries through a comprehensive literature analysis. An analytical review was conducted, examining data from peer-reviewed studies sourced from Scopus, Web of Science, and PubMed. Inclusion criteria encompassed genetic, biomechanical, radiographic, and cross-sectional studies on non-elite runners, including children and adolescents. Key metrics analyzed included navicular height, arch height index, calcaneal inclination angle, and toe and MTP joint strength, all in relation to injury risk. Data were analyzed descriptively and through correlations using Pearson correlation and logistic regression models. The findings indicated that flat feet are associated with higher instances of plantar fasciitis and shin splints, while cavus feet present an increased risk for stress fractures and tendinopathies due to inadequate shock absorption. Individuals with weak intrinsic foot muscles exhibited poor arch support, heightening injury susceptibility. Notably, 137 SNPs were linked to connective tissue, neuromuscular, and inflammatory disorders affecting arch morphology, with sex and BMI identified as significant outcome factors. Arch structure and intrinsic muscle strength are critical risk factors for overuse injuries. The study emphasizes the need for injury prevention strategies that integrate biomechanical assessments, muscle strengthening, and genetic evaluations.